The concept of connect Karczew to the railway network - Szymon Klemba; Adam Dąbrowski (Przegląd Komunikacyjny)
Abstract: The article concerns railway network extension towards Karczew town in aspect of a railway connection to Warsaw. The first part presents how the public transport in Karczew has functioned over the years and current bus service is also described. Then functional variants of new railway line are described. In the article each proposed variant of the line is presented. The possibilities and threats related to the implementation of the concept are analyzed. In the summary the direction of further study works was indicated.